Corpus-based analysis of shifts in China’s diplomatic stance across seven decades (1949–2018) - Tian, Xujun; Li, Xiaoqian (Frontiers in Psychology, 2022)
Using critical discourse analysis, this study investigates the changes in China’s diplomacy in the past seven decades based on the diachronic corpus of Chinese diplomatic discourse over 1949–2018. Adopting a corpus-based approach with a mixed-methods analysis, it examines the key keywords and keywords in these seven periods of Chinese diplomatic discourse and their significant collocations. The results show that China has worked with the United States, Japan, the United Kingdom, and some Asian, Latin American, and African countries to safeguard world peace, while opposing war, establish good relations with other countries, and promote mutual development through cooperation. In addition, China’s diplomacy has experienced politics-oriented and economy-oriented eras and is now in an era of global sustainable development. Chinese diplomatic discourse is the linguistic representation of China’s diplomacy, which is fundamentally determined by its national interests as well as its changing social and historical situations domestically and internationally.